Ultraviolet Radiation Cured Bio-Fibre Composites From Oil Palm Empty Fruit Bunch. - Falza, M.A.; Kumar, R.N.; Rozman, H.D. (2003)
In this study, development of ultra-violet (UV) cured biofibre composites is reported. The composites were based on the pulp made from empty fruit bunch (EFB) as the reinforcing agent and unsaturated polyester as the matrix.